2006
DOI: 10.1152/ajpheart.00803.2005
|View full text |Cite
|
Sign up to set email alerts
|

Axial nonuniformity of geometric and mechanical properties of mouse aorta is increased during postnatal growth

Abstract: The hemodynamic conditions of aorta are relatively uniform prenatally and become more heterogeneous postnatally. Our objective was to quantify the heterogeneity of geometry and mechanical properties during growth and development. To accomplish this objective, we obtained a systematic set of data on the geometry and mechanical properties along the length of mouse aorta during postnatal development. C57BL/6 mice of ages 1-33 days were studied. The ascending aorta was cannulated in situ and preconditioned with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 32 publications
11
84
1
Order By: Relevance
“…The current study and an aging study in Eln ϩ/Ϫ mice (20) suggest that blood pressure begins increasing compared with WT in late postnatal development and continues to increase with aging. The measured blood pressures for WT mice in this study are consistent with previous data (12). Blood pressure is significantly increased in Eln ϩ/Ϫ mice at P14, which is later in development than significant reductions in the aortic pressurediameter and -compliance relationships at P7, supporting our hypothesis that changes in mechanical properties precede changes in blood pressure in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…The current study and an aging study in Eln ϩ/Ϫ mice (20) suggest that blood pressure begins increasing compared with WT in late postnatal development and continues to increase with aging. The measured blood pressures for WT mice in this study are consistent with previous data (12). Blood pressure is significantly increased in Eln ϩ/Ϫ mice at P14, which is later in development than significant reductions in the aortic pressurediameter and -compliance relationships at P7, supporting our hypothesis that changes in mechanical properties precede changes in blood pressure in these mice.…”
Section: Discussionsupporting
confidence: 91%
“…Huang et al (2006) showed a linear relationship in the outer (figure 14a) and inner diameter (data not shown) of the aorta with age. The growth rate of both the outer and the inner diameters of thoracic and abdominal aorta are different during the first two weeks of life (Huang et al 2006). 6.3.2.…”
Section: Postnatal Developmentmentioning
confidence: 88%
“…The longitudinal retraction or pre-stretch is small in the young and increases with postnatal growth and development as the vessels are stretched by body growth (Dobrin et al 1975;Huang et al 2006). Zhang et al (2005) found that under the same physiological pressure, a more similar magnitude of circumferential and longitudinal stresses may be obtained by prestretching the vessel.…”
Section: Effect Of Longitudinal Pre-stretchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigate the morphological, structural, and biochemical changes of the aorta as well as the relation between these changes and the mechanics of the aorta, see [9,16,20,32,33]. These studies confirm that the aorta increases its stenosis ratio, wall thickness, and mechanical stiffness during atherosclerosis.…”
Section: Introductionmentioning
confidence: 77%